AN ANALYSIS OF TEACHERS’ STRATEGIES IN TEACHING READING COMPREHENSION - Ulfa, Andi Afifatul; Jabu, Baso; Ariyani, Amra (Universitas Negeri Makassar, 2022)
The purpose of this research is to analyze the strategies used by teachers to teach reading comprehension and the factors that influence teachers in choosing strategies for teaching reading comprehension. The subjects of this study were English teachers at SMPN 9 Makassar. This type of research is designed as qualitative descriptive research. To collect data in research, the researcher uses interviews. The data obtained have been processed in several ways, the first is data reduction, data display, and conclusion drawing. The results of the research found that the strategies used by teachers in teaching understanding were Scaffolding, Reciprocal Teaching, and QARs (Question-Answer Relationships). In choosing a strategy to teach reading comprehension, researchers found three factors that influence teachers in choosing teaching strategies, namely characteristics of students, teaching materials, and the teacher's knowledge of the strategy to be used.